BUILD AN ATTITUDE OF NATIONALSM STUDENTS AT SDN 7 KADIPATEN WITH THE METHOD OF DISCUSSION IN THE SUBJECT PPKN - T Heru Nurgiansah (Jurnal Serunai Pancasila dan Kewarganegaraan, 2020)
AbstractThe research aims to determine the increase in nationalism through learning of PPKn-in to the discussion method of class VI students of SDN 7 duchy. This class action research uses quantitative methods. Conclusion of the research result is the level of student nationalism through learning PPKn with the method of discussion on students of class VI SDN 7 Duchy is very good. A student nationalism before being given an action of 45.93%, after being given action in the I-cycle gained by 54.08%, was on cycle II acquired by 84.89% or very good. Nationalism in the study of PKN, associating the lesson material with the usual things observed and experienced by students daily, so that students learn to reconstruct a new knowledge and skills when students study. PKn learning requires learning interactions.Keyboard: naionalism, discussion, PPKn,